Efeito túnel multidimensional em reações nucleares - Agrello, Deise Amaro [UNESP] (Universidade Estadual Paulista (Unesp), 1992)
The quantum tunneling through a potential barrier in several dimensions is discussed and three diferent problems are studied. Firstly the tunneling problem through two dimensional barrieers is studied using quantum mechanical methods. We consider the collision of two Ni isotopos at energies near the top of the barrier of 100 Mev. The reflection and transmission coefficients are found through a coupled channel calculation. We have considered up to five open channels in the numerical calculations and have found that if the number of channels is increased further the results change only slightly. A different kind of coupling between the degrees of freedom from those found in the literature is proposed and the effect of this coupling in the barrier region is studied. The sub-barrier fusion reaction cross section is also calculated and our results are compared with the data and other results found in the literature. The second problem is the spontaneous emission of nuclei havier than the alpha particle. The emission of 'INTPOT. 14 C' from 'INTPOT. 223 Ra' recently observed is discussed and the penetrability factors are calculated. The ratio of the preformation factor for the'INTPOT. 14 C' emission relative to the emission of the alpha particles by the 'INTPOT. 223 Ra' is studied. Considering a realistic potential barrier we compare our results for penetrability factors and preformation factors with other recently found in the literature. Then, the size of the nuclear radius in the exotic decay theory is studied, considering several reactions where decays of nuclei heavier than the alpha particle have been observed. Finally the alpha clustering in nuclei is considered. Using a simple cluster model some nuclear properties of the 'INTPOT. 43 Ti' are studied, as wave functions, energy levei schemes and decay widths. Two different kinds of semiclassical approximations are considered to study the wave functions and the quantum...

Discutimos nesta tese o efeito túnel através de uma barreira de potencial em várias dimensões e aplicamos a três problemas diferentes. Primeiramente estudamos o problema de tunelamento através de barreiras em duas dimensões usando métodos quânticos. Consideramos a colisão de dois isótopos de Ni à energias em torno da altura da barreira na região de 100 MeV. Encontramos os coeficientes de reflexão e transmissão fazendo um cálculo de canais acoplados. Nos cálculos numéricos consideramos até cinco canais abertos e encontramos que se o número de canais é aumentado, os resultados variam apenas ligeiramente. Propomos neste trabalho um tipo de acoplamento entre os graus de liberdade diferente daqueles existentes na literatura e estudamos o efeito deste acoplamento na região da barreira. Calculamos também a secção de choque de fusão e comparamos os nossos resultados com os experimentais e com outros encontrados na literatura. 0 segundo problema considerado é a emissão espontânea de núcleos mais pesados que a particula alfa. Discutimos a emissão de 'INTPOT. 14 C' do 'INTPOT. 223 Ra' que foi recentemente observada e calculamos os fatores de pré-formação. Estudamos a razão dos fatores de pré-formação para a emissão do 'INTPOT. 14 C' relativa à emissão da particula alfa do 'INTPOT. 223 Ra'. Consideramos uma barreira de potencial realistica, comparamos nossos resultados para os fatores de penetrabilidade e os fatores de pré-formação com outros encontrados recentemente na literatura. À seguir fazemos um estudo do tamanho do raio nuclear na teoria de decaimento exóticos, considerando as várias reações onde decaimentos de núcleos mais pesados que a particula alfa já foram observados. Finalmente, consideramos a formação de aglomerados alfa em núcleos. Usando um modelo de cluster simples, estudamos algumas propriedades nucleares do 'INTPOT. 44 Ti', como por exemplo, as funções...
Keywords: Tunelamento (Física); Reações nucleares; Tunneling (Physics)